Vitamin C and Nonylphenol Alters Some Apoptotic Gene Expression Levels In Rats - Zemheri-Navruz, Fahriye; Erdogan, Metin; Uguz, Cevdet (International Journal of Scientific Research in Biological Sciences, 2021)
Alkylphenol ethoxylates (APEs) are ubiquitous enviromental pollutants and have been shown to mimic 17?-estradiol. Nonylphenol (NP) is a biodegradation product of APEs. NP is the most abundant in the environment and the most resistant against biodegration among other APEs dervivatives. In this study, against the effects of apoptosis induced by NP, potential preventive effects of vitamin C for gene expression levels was investigated in Rattus norvegius’s. NP was administered in the amounts of 0.1, 10, 1000 µg/ml alone and in combination with 100 µg/ml vitamin C to the 5 male and 5 female Rattus norvegius. To determine the level of changes in the gene expression levels in brain and liver tissues at real-time PCR. Results indicated that NP caused a significant increase in the expression caspase-3 and bcl-XL gene while it caused a significant decrease in the expression of bcl-2 and p53 genes in a dose dependent manner. In conclusion, while NP induced the expression of apoptotic gene, it inhibited anti-apoptotic genes and vitamin C had been shown to accelarate the NP-induced effects in both cases.